Dissolution enhancement of Gefitinib by solid dispersion and complexation with β-cyclodextrins: In vitro testing, cytotoxic activity, and tablet formulation - Adel F. Alghaith; Gamal M. Mahrous; Ahmed S. Alenazi; Suliaman M. ALMufarrij; Mohammed S. Alhazzaa; Awwad A. Radwan; Abdullah S. Alhamed; Mohamed S. Bin Salamah; Sultan Alshehri (Elsevier, 2024)
Cancer is the leading cause of mortality worldwide. In patients with metastatic non-small cell lung cancer, epidermal growth factor receptor (EGFR) is often overexpressed. Gefitinib (GEF), an inhibitor of EGFR, is approved for the treatment of patients with metastatic non-small cell lung cancer (NSCLC). However, the low solubility and dissolution of GEF limits its bioavailability. Numerous methods, including solid dispersion (SD) and complexation, have been reported to enhance the dissolution of poorly soluble drugs. In this study, GEF complexes were prepared using methyl-β-cyclodextrin (MβCD) and hydroxypropyl-β-cyclodextrin (HPβCD) in two molar ratios (1:1 and 1:2), furthermore, GEF SDs were prepared using polyvinylpyrrolidone (PVP), polyethylene glycol (PEG), and poloxamer-188(PXM) in three different ratios (1:2, 1:4 and 1:6 w/w). Dissolution studies were conducted on the prepared formulations. Dissolution results showed a 1.22-2.17-fold enhancement in drug dissolution after one hour compared to untreated GEF. Two formulations that showed higher dissolution enhancement were subsequently evaluated for in-vitro cytotoxicity and were formulated into tablets. The selected PVP-GEF (1:4 w/w) and MβCD-GEF (1:1M) formulas displayed improved cytotoxicity compared to untreated GEF. The IC50 values of the PVP-GEF and MβCD-GEF were 4.33 ± 0.66 and 4.84 ± 0.38 µM, respectively which are significantly lower (p < 0.05) than free GEF. In addition, the formulated tablets exhibited enhanced dissolution compared to pure GEF tablets. PVP-GEF SD tablets released (35.1 %±0.4) of GEF after one hour, while GEF-MβCD tablets released (42.2 % ± 0.7) after one hour. In the meantime, tablets containing pure GEF showed only 15 % ± 0.5 release at the same time. The findings of this study offer valuable insights for optimizing the dissolution and hence therapeutic capabilities of GEF while mitigating its limitations.